INTERVENTION OF THIRSTY IN CONGESTIVE HEART FAILURE (CHF) PATIENTS TO INCREASED ADHERENCE OF FLUID RESTRICTION: A SYSTEMATIC REVIEW - DIAN HUDIYAWATI (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2017)
Introduction. Thirst is a common symptom of chronic heart failure (CHF) patients. Difficulties to adherence with fluid restrictions are among the effects of thirst in HF patients and therefore have an impact on worsening condition, but intervention studies aimed specifically at reducing thirst in CHF are lacking.Purpose. Purpose of this manuscript is to assess the effective intervention to reduce thirst intensity in CHF patients.Methods. Medline, Pubmed, EBSCO and hand search were searched using the key words thirst, intervention, heart failure, CHF, fluis restriction, therapy.Result.  Eighteen articles were found, six studies were inluded. Any kind of interventions in each articles, include: drink cold water 5oC, chewing gum, saliva substitute, sucking ice cubes and three bundle of interventions (oral swab, water sprays and menthol moisturizer).Conclusions. The most effective interventions to alleviate thirst was sucking ice cubes. But, no intervention studies were found in congestive heart failure patients. So investigations in people with heart failure is needed. Keywords: thirst, intervention, heart failure, systematic review